(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Present paper is a profound study about the themes present in Jane Rhys’s ‘Wide Sargasso Sea’. The novel is written with an Anti - Imperialism and colonialism viewpoint but the research paper is an attempt to search the other main themes that are present in the novel. The paper aims to analyze the themes under the perspective of slavery and the changes that were taking place in the Caribbean after the abolishment of slavery. The research paper also intends to study the persisting abhorrence, hatred and abusive relationship between the Westerners and native Jamaicans.